Plasma iron, zinc, and copper levels in heart disease patients in Dr. Sardjito Hospital Yogyakarta - Pramudji Hastuti, Lukman Endro HAH Asdie, Tri Hartati ASM Sofro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Heart disease is a major cause of death in both men and women in industrialized countries. In fact, many individuals,who develop heart disease, have normal cholesterol and blood pressure levels. It suggests that other risk factorsmay also play a role. Iron (Fe), zinc (Zn) and copper (Cu) may promote CHD by increasing lipid peroxidation andcausing oxidant-induced damage in various organs. These minerals are essential as cofactors for functional enzymesin the body. The hypothesis that Fe and Cu depletion protects against ischemic heart disease has generated significantdebate, but this hypothesis cannot be rejected until stronger evidence that high Fe stores increase the incidence ofCHD or death from myocardial infarction is proven. This research was aimed to find out the levels of Fe, Cu, and Znplasma as risk factors for heart disease patients, compared with those in hyperlipidemic patients and controls. Inthis study, we examined the Fe, Zn and Cu levels in plasma of CHD patients, hyperlipidemic patients, and healthycontrols by atomic absorption spectrophotometer. Thirty five CHD patients, 31 hyperlipidemic patients, and 26healthy controls. Age, body weight, body height, BMI, systolic and diastolic blood pressure of each group were notsignificantly different (p>0.05). There were higher cholesterol and lower HDL-C levels in CHD patients comparedwith those in hyperlipidemic patients and controls. Therewere significantly higher triglyceridemia level in hyperlipidemicpatients compared to those in CHD patients and controls. Iron level in CHD patients were not significantly differentthan those in hyperlipidemic patients and controls. Zinc level in CHD patientswere not significantly different comparedwith those in controls, but in hyperlipidemic patients, they were significantly lower than those in CHD patients andcontrols. Copper level in CHD and hyperlipidemic patients were significantly lower than those in controls. In thisresearch, it could be concluded that the decrease in Cu level might be one of the risk factors of CHD.Keywords : iron-zinc-copper-heart disease-risk factor